Kap Survey on Management Of Defective Composite Restorations Among Dental Practitioners In Chennai - B, AMRITHAA.; HARIPRIYA, S.; GEETHA, R.V. (The journal of contemporary issues in business and government, 2021)
Background :Development of dental materials plays a significant role in dental practice from mechanically focused to a more biologically focused dentistry. Repair or replacement of dental restorations is one of the most common procedures performed by the dental practitioners. Defective composite restoration was replaced but more conservative treatment like repair has been advocated in the recent past. Aim :The aim of the present study is to investigate the knowledge, attitude and practice on management of defective composite restoration among dentists in chennai. Methods :A cross-sectional questionnaire based study was conducted in 2020 among dental practitioners in chennai. Survey questionnaires were prepared, using an online survey portal and it was distributed randomly to 105 dentists via google forms. The obtained results were statistically analysed using SPSS and the graphs were plotted. Results :Majority of the participants considered that repair was less time consuming and most of the respondents agreed that repair increased the longevity of a previously restored defective composite restoration. The obtained results state that repair of composite restoration is practiced more widely than replacement.There was no significant association between the field of practice of the dentists (specialists/ general practitioners) and their response to the question for the majority of the survey questions Conclusion :Based on the results of this survey, majority of dentists perform repair of composite restoration rather than replacement to treat small defects in composite restoration.